Imperative role of applied potential and inorganic carbon source on acetate production through microbial electrosynthesis. (September 2016) - Mohanakrishna, Gunda; Vanbroekhoven, Karolien; Pant, Deepak
Graphical abstract: Highlights: A long term study for 190 days was performed for microbial electrosynthesis. CO2 and bicarbonate were evaluated as substrates for acetate production. Continuous and batch operations showed their role on acetate production rate and pH. Factors influencing stability and reproducibility were identified. Abstract: Microbial electrosynthesis (MES) is a novel technology that produces organic molecules from the reduction of carbon dioxide (CO2 ) at biocathode. MES system is a hybrid device that combines components of biological and fuel cells in a single system for chemicals/energy generation from inexpensive substrates. Present study evaluates the influence of cathodic potentials (−800 mV and −600 mV) on reduction of CO2 to acetate using enriched acetogenic bacteria as the biocatalyst at 30 °C using graphite and VITO carbon electrodes as cathode and anode respectively. The first stage of evaluation of bicarbonate as carbon source was continued to second stage where gaseous CO2 used as C source. In both the stages −800 mV showed higher acetate production efficiency. MES reactor with cathodic potential of −800 mV showed 4.05 and 5.45 g acetate/L respectively during first and second stage. Changing the carbon source of the systems from bicarbonate to CO2 positively influence the performance. Moreover, change in operation mode from continuous to batch resulted in improved acetate production rate, which also proved that the performance was reproducible and stable. Continuous CO2 supply maintained the pH near neutral which might explain the traces of ethanol produced in the system. Higher coulombic efficiency was also registered with −800 mV operation than −600 mV.